Art, Sex and the State: a Reflection on Certain Encounters between Philosophical Thinking and the Real World - Adlam, Robert (Philosophy and Realistic Reflection, 2025)
This paper stems from the author’s practical experiences in relation to the provision of educational opportunities and the facilitation of organizational development in a number of very different institutions and real-world settings. Contrasts between the realm of philosophical inquiry and that of people in their more usual contexts of practice are noted. Basic aspects of the nature of the ‘real world’ are outlined whilst the fact that philosophy has touched and influenced a great many aspects of the actual human condition is underlined. Murdoch’s observation that philosophy is an ‘unnatural activity’ is referenced in order to sharpen the distinction between our everyday forms of discourse and those particular to philosophy itself. The reach and impact of philosophy is demonstrated as the paper moves on to consider how the fruits of philosophical thinking have come to shape a) the practices of an advanced contemporary form of art b) the appreciation rather than the denigration of human sexual behavior, and c) the emergence of recent totalitarian states - along with a note about the ideology of ‘the American dream’. The specific examples included in the text invite further reflection on how philosophical thinking, either directly or indirectly, influences many other aspects of human existence and experience. The paper concludes with a sobering observation about the recurring human tendency to allow individual and communal desire to triumph over the achievements of reason. Written in a deliberately accessible style, the paper is intended to appeal to a readership beyond that of the philosophical community